Decarbonylative Radical Coupling of α‐Aminoacyl Tellurides: Single‐Step Preparation of γ‐Amino and α, β‐Diamino Acids and Rapid Synthesis of Gabapentin and Manzacidin A1. Issue 5 (10th December 2014) - Nagatomo, Masanori; Nishiyama, Hayato; Fujino, Haruka; Inoue, Masayuki
Abstract A new radical‐based coupling method has been developed for the single‐step generation of various γ‐amino acids and α, β‐diamino acids from α‐aminoacyl tellurides. Upon activation by Et3B and O2 at ambient temperature, α‐aminoacyl tellurides were readily converted into α‐amino carbon radicals through facile decarbonylation, which then reacted intermolecularly with acrylates or glyoxylic oxime ethers. This mild and powerful method was effectively incorporated into expeditious synthetic routes to the pharmaceutical agent gabapentin and the natural product (−)‐manzacidin A.